PENTINGNYA PERENCANAAN SUMBERDAYA MANUSIA DALAM SEBUAH ORGANISASI - Muzayyanah Jabani (MUAMALAH, 2015)
In the face of increasingly fierce business competition along with the increasing progress of science and technology today, Human Resources is an asset of the organization / company that is not replaceable. Sophistication and technological progress becomes meaningless if there is no human element in it as the executor / actors in operating these technologies. Technological developments that occur at this time still remains to be in need of human resources capable of applying these technologies into organizational practices. What kind of quality of human resources and the number (quantity) of how an organization / company must recruit and hire, the need for human resource planning system is good and reliable. HR planning is an effort to projecting how many employees and employee organizations such as what is needed in the future. All organizations / companies should determine his future with various plans that are relevant to the demands of time. The era like today, the future is very unpredictable because of changes that occur very quickly and massively. In the conditions of an environmental competitive business, life business organizations are required to continue moving with the flow of rapid change and massive. The swift currents of change bring a logical consequence for the company to always anticipate and must be able to adjust to the changes. In this context, human resource planning will become more important for companies because of globalization, new technologies, and the process of organizational restructuring have overshadowed the life of the organization. Organizations that are not supported employee / employees who fits both from the aspect of quantity, quality, strategy, and operations are good, then certainly these organizations will be difficult to maintain and develop its presence in the future for the implementation of human resources planning can succeed, at least there are four aspects planning that must be considered / done that: (1) how the projected number of employees needed (forecasting of employees), (2) identifying the human resources available in the organization (human resource audit), (3) to analyze the balance of supply and demand (demand and supply analysis), (4) runs a program of action (action program).